Understanding head impact exposure in male and female Amateur Olympic boxers - Jones, C.; Melotti, L.; Brown, M. R.; Loosemore, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Amateur boxing is a high-intensity intermittent combat sport, which results in the accumulation of sub-concussive head impacts during competition. It has been debated in a number of combat and collisions sports that the result of repetitive head impact exposure is associated with long term neurodegeneration. There is currently a gap in understanding the relationship between head impacts and neurological function due to a lack of quantification of forces that individuals are exposed to in competition. This study aimed to characterize impact exposure and the associated injury metrics of amateur male and female international boxers during an Olympic qualifying competition via an instrumented mouthguard monitoring system.